Analysis of Social and Emotional Development of Orphaned Youth in terms of Self Concept and Resilience: Study at Child Care Children's Home (PSAA) Tunas Bangsa Pati - Santoso, Santoso; Zamroni, Edris (Universitas Muhammadiyah Metro, 2017)
The purpose of this study is to describe the development of the Young Social and Emotional Self-concept and in terms of resilience in the PSAA Tunas Bangsa Pati. The method used is descriptive research with development studies dab types of data obtained will be analyzed by the cross sectional method. The results showed that the concept of self-possessed teenager PSAA is not good, it can be seen from the description of several indicators of self-concept which suggests that adolescents assessment of him is not good because many feel insecure and feel inferior. Viewed from the aspect of resilience, generally adolescents PSAA good enough. It can be seen from the emotion management capabilities of any events that are considered less fun in.